Perbedaan Satuan Lingual -a, -na, dan –ana Wacana Khotbah Jumat dalam Bahasa Jawa - Wening Handri Purnami (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2016)
The impertive signs on Friday sermon discourse in Java language are in affix form, namely in form of –a, –na, and –ana suffixes. It is hypothesised that the suffixes of –a, –na, and –ana are alomorf of of –a. The objective of this researcher is to describe the differences of suffixes of –a, –na, and – ana found on Friday Sermon in Java language. The data in this research were gathered through observation and note taking techniques, while both structural and discourse theory were used in analyzing the data. The result of the research shows that the imperative signs on Friday Sermon discourse in Java language are in suffixes form, namely –a, –na, and –ana which are found on basic words of eling’remember’, weruh ‘understand’,jaga ‘keep’, jupuk ‘take’. adoh ‘far’, weneh ‘give’, goleh ‘puppet’, and sedekah ‘alms' expressing different meaning.